Keep calm and trade on: China's decisive role in agricultural markets under turmoil - Lena Kuhn; Tinoush Jamali Jaghdani; Sören Prehn; Zhanli Sun; Thomas Glauben (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2022)
International agricultural trade is key to improving global food security. It ensures access to more diversified foods (e.g. Krivonos and Kuhn 2019 ), acts as a safety net against local production shortfalls (Glauben et al. 2022) and helps make use of regional climatic or resource-related production advantages. While local production and short supply chains can reduce transport costs, they do not necessarily equate to resilient food systems or lower carbon footprints (Stein and Santini 2022). Currently, though, international agricultural trade is facing supply chain disruptions and rising world market prices resulting from the ongoing Covid-19 pandemic, increasing global food demand and extreme weather events. Both are threatening already strained food security, in particular in import-dependent, low-income regions. Geopolitical risks, such as the China- US trade war and Russia's invasion of Ukraine, are further rattling the food market. As the world's largest consumer of agricultural goods, China's trade strategies influence world markets, with ripple-down effects for consumers around the world, particularly in the Global South. This policy brief aims at shedding light on China's current market actions, and the likely short- and mid-term developments and their impacts. We argue for moderation in response to short-term shocks. Excessive mobility and trade restrictions as well as extreme stockpiling should be avoided. These harm the trade system's overall capacity to resist further and more serious global challenges related to population growth and climate change.
urn:nbn:de:gbv:3:2-911772
Keywords: 330